1996
DOI: 10.1152/ajpheart.1996.271.5.h1988
|View full text |Cite
|
Sign up to set email alerts
|

Arginase activity in endothelial cells: inhibition by NG-hydroxy-L-arginine during high-output NO production

Abstract: Rat aortic endothelial cells were found to contain both constitutive and lipopolysaccharide (LPS)-inducible arginase activity. Studies were performed to determine whether induction of nitric oxide synthase (NOS) by LPS and cytokines is accompanied by sufficient arginase induction to render arginine concentrations rate limiting for high-output NO production. Unactivated cells contained abundant arginase activity accompanied by continuous urea formation. LPS induced the formation of both inducible NOS (iNOS) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
213
2
9

Year Published

1998
1998
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(236 citation statements)
references
References 0 publications
12
213
2
9
Order By: Relevance
“…Consistent with this hypothesis, increased vascular arginase activity was reported to contribute to decreased endotheliumdependent NO production in pathologic conditions such as hypertension (19,20), atherosclerosis (21), diabetes (22), and erectile dysfunction (23), or in aging (24). Moreover, even though the regulating factors of arginase expression/activity remain largely unknown, it was demonstrated that various proinflammatory cytokines can act as inducers of arginase expression in cultured endothelial cells (18,25,26).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Consistent with this hypothesis, increased vascular arginase activity was reported to contribute to decreased endotheliumdependent NO production in pathologic conditions such as hypertension (19,20), atherosclerosis (21), diabetes (22), and erectile dysfunction (23), or in aging (24). Moreover, even though the regulating factors of arginase expression/activity remain largely unknown, it was demonstrated that various proinflammatory cytokines can act as inducers of arginase expression in cultured endothelial cells (18,25,26).…”
mentioning
confidence: 77%
“…Both arginase isoforms are expressed by endothelial and vascular smooth muscle cells (18). Because NOS and arginase use L-arginine as a common substrate, arginase may down-regulate NO biosynthesis by competing with NOS for L-arginine degradation.…”
mentioning
confidence: 99%
“…In contrast, type II arginase, a mitochondrial enzyme, is expressed at lower levels in kidney, brain, small intestine, mammary gland and macrophages, but there is little or no expression in liver [138,162,198,199]. Rat aortic endothelial cells and murine macrophages express both type I and type II arginases [200][201][202], and it is likely that other cell types also express both isoenzymes. The different subcellular localization of the arginase isoenzymes may provide a mechanism for regulating the metabolic fate of arginine, as postulated for enterocytes [203].…”
Section: Arginasementioning
confidence: 99%
“…For example, iNOS-expressing macrophages [228,229] and endothelial cells [200] can produce sufficient N G -hydroxyarginine to inhibit arginase activity. Because endothelial cells in intact animals are constantly perfused, whereas cultured cells are not, it is not clear whether the former would be exposed to sufficient N G -hydroxyarginine in i o to inhibit cellular arginase activity.…”
Section: Arginase and No Synthesismentioning
confidence: 99%
See 1 more Smart Citation